CBL/CAP Is Essential for Mitochondria Respiration Complex I Assembly and Bioenergetics Efficiency in Muscle Cells - Aye Cho-Cho; Hammond Dean E; Rodriguez-Cuenca Sergio; Doherty Mary K; Whitfield Phillip D; Phelan Marie M; Yang Chenjing J; Perez-Perez Rafael; Li Xiaoxin; Diaz-Ramos Angels; Peddinti Gopal; Oresic Matej; et al. (MDPI, 2025)
CBL is rapidly phosphorylated upon insulin receptor activation. Mice whole body CBL depletion improved insulin sensitivity and glucose clearance; however, the precise mechanisms remain unknown. We depleted either CBL or its associated protein SORBS1/CAP independently in myocytes and assessed mitochondrial function and metabolism compared to control cells. CBL- and CAP-depleted cells showed increased mitochondrial mass with greater proton leak. Mitochondrial respiratory complex I activity and assembly into respirasomes were reduced. Proteome profiling revealed alterations in proteins involved in glycolysis and fatty acid degradation. Our findings demonstrate CBL/CAP pathway couples insulin signaling to efficient mitochondrial respiratory function and metabolism in muscle.